DYNAMIC POWER MANAGEMENT SCHEME FOR BI-DIRECTIONAL DC-DC CONVERTERS USING HESS (International Journal of Food and Nutritional Sciences, 2022)
Hybrid Energy Storage Systems (HESS) technologies are used to supplement batteries in systems such as electric/hybrid automobiles and islanded DC microgrids. To maintain constant DC grid, balance the energy flow between source and load. Energy storage is used to correct any mismatches between supply and demand. The battery-SC combination is the best suitable for managing the imbalance power between source and load demand. The modelling of HESS, design of converter, stability study are presented. The simulation results for traditional and suggested technique for step change in PV and load demand are all examined in this article. The effectiveness of traditional and proposed control strategies was evaluated